(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
The dialectical behavior therapy (DBT) is a clinical protocol originally developed for the treatment of suicidal and parasuicidal behaviors, and later extended to psychopathology as the borderline personality disorder. Treatment involves learning prerequisites behaviors, divided in stages (1) “attaining basic capacities” (2) “reducing postttraumatic stress” and (3) “increasing self-respect and achieving individual goals”. This article examines whether and how DBT meet the philosophical and applied criteria for inclusion in therapies based on behavior analysis. We revised philosophical conception basis as well as the assessment and intervention strategies. It is argued that the philosophical foundation approaches behaviorism, due to its behavior definition, conceptions of causes and selection. We also identified assessment and intervention strategies, focusing on acceptance and change, based on functional analysis, reinforcement and shaping for learning new skills.